2022
DOI: 10.1021/acs.est.2c02227
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline-Induced Release and Oxidation of As(III) Coupled with Concomitant Ferrihydrite Transformation

Abstract: Cocontamination with tetracycline (TC) and arsenic (As) is very common in paddy fields. However, the process and underlying mechanism of arsenite (As­(III)) transformation on iron mineral surfaces in the presence of antibiotic contaminants remain unclear. In this study, the release and oxidation of As­(III) on ferrihydrite (Fh) surfaces and Fh transformation in the presence of TC under both aerobic and anaerobic conditions were investigated. Our results indicated that the TC-induced reductive dissolution of Fh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…The reaction between Fe­(II) and H 2 O 2 (eq ) produced Fe­(IV) in near neutral or alkaline conditions, which can also induce As­(III) oxidation. , PMSO was selected as the quencher of Fe­(IV). Since both •OH and Fe­(IV) can oxidize PMSO ( k PMSO, • OH = 3.61 × 10 9 M –1 ·s –1 , k PMSO, Fe(IV) = 1.23 × 10 5 M –1 ·s –1 ), overdosed MeOH was added together with PMSO to exclude the effect of • OH .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction between Fe­(II) and H 2 O 2 (eq ) produced Fe­(IV) in near neutral or alkaline conditions, which can also induce As­(III) oxidation. , PMSO was selected as the quencher of Fe­(IV). Since both •OH and Fe­(IV) can oxidize PMSO ( k PMSO, • OH = 3.61 × 10 9 M –1 ·s –1 , k PMSO, Fe(IV) = 1.23 × 10 5 M –1 ·s –1 ), overdosed MeOH was added together with PMSO to exclude the effect of • OH .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some antibiotic molecules can complex with surface Fe­(III) of iron minerals and that electron transfer within the complex induces the reduction of Fe­(III) and the degradation of antibiotics. , It was presumed that TCs can play the same role as these organic molecules, promoting the generation of ROS and contributing to the oxidation of co-existing As­(III). A recent study reported that TTC induced the reductive dissolution of ferrihydrite (Fe­(II) release) and led to the release and oxidation of As­(III) adsorbed by ferrihydrite in both aerobic and anaerobic conditions . Competitive adsorption of TTC significantly promotes the release of As.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing toxicity and complexity due to the combined pollution of heavy metals and antibiotics in aqueous media, arising from worldwide urbanization and industrialization, is causing public concern over environmental issues. As a result of natural and anthropogenic activities including waste discharge, rock weathering, and mining, high levels of arsenic (up to 1350 μg/L) have been frequently detected in groundwater in the northwest of China, for example, Inner Mongolia, Xinjiang Uighur, and Guizhou province, which markedly exceed the detection limit (10 μg/L) set by the World Health Organization (WHO) . Meanwhile, in the rural areas contaminated by arsenic, pharmaceutical antibiotics (e.g., tetracycline) used for animals and humans to treat infectious diseases are often directly released into domestic sewage, which will be reutilized for irrigation of farmland and inevitably lead to the antibiotic pollution of groundwater. , Excessive and long-term exposure to heavy metals and antibiotics can adversely affect the growth of animals and plants and even cause a series of health-related problems such as cancer, neurotoxicity, and chronic kidney disease through migration and the food chain. Recent studies have demonstrated that the presence of tetracycline could reduce the immobility of arsenic in aqueous solutions, and meanwhile, the presence of high concentrations of arsenic also inhibited the removal of tetracycline. ,, Undoubtedly, their interactive behavior adversely affects the overall treatment efficiency. Therefore, the simultaneous removal of arsenic and tetracycline is of great necessity but remains a significant challenge in the water treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…4 Meanwhile, in the rural areas contaminated by arsenic, pharmaceutical antibiotics (e.g., tetracycline) used for animals and humans to treat infectious diseases are often directly released into domestic sewage, which will be reutilized for irrigation of farmland and inevitably lead to the antibiotic pollution of groundwater. 5,6 Excessive and long-term exposure to heavy metals and antibiotics can adversely affect the growth of animals and plants and even cause a series of health-related problems such as cancer, neurotoxicity, and chronic kidney disease through migration and the food chain. 7−10 Recent studies have demonstrated that the presence of tetracycline could reduce the immobility of arsenic in aqueous solutions, and meanwhile, the presence of high concentrations of arsenic also inhibited the removal of tetracycline.…”
Section: Introductionmentioning
confidence: 99%